An exploration of neglected themes in the development of domestic violence perpetrator programmes in the UK - Morran, David Charles (2019)
This thesis is based on a body of published work which critically examines the major influences on the development of domestic violence perpetrator programmes in the UK. The thesis explores how a series of evolving theoretical frameworks, social policy, and organisational contexts have influenced approaches to practice with perpetrators, and how programme effectiveness has been variously determined and assessed. The origins of the papers and the linking narrative developed from a sense of professional dissatisfaction that several important themes concerning programmes and the potential for them to engage more effectively with perpetrators have frequently been overlooked or marginalised in the research literature. These themes concern the wider social contexts in which perpetrator programmes in the UK emerged, the explanations for men’s violence and abuse which have variously prevailed, and the practices adopted in programmes as a consequence. They note the extent to which various protagonists including feminist activists, social policy professionals, academic researchers and probation and social work managers have often conceptualised perpetrator programmes as abstract entities. Consequently, this thesis addresses a number of important and original themes. It addresses and emphasises the importance of relationships between programme practitioner and participant, significantly acknowledging the emotional impact upon practitioners of undertaking complex work in an innovative and demanding area. It takes into account the significance of the wider social, structural and cultural circumstances in which programmes function. It also examines the neglected question of what desisting from domestic abuse might actually entail as well the rewards and challenges involved. It explores how men who have perpetrated violence and abuse might better be enabled to desist from this behaviour and live more positive lives and discusses the implications for programmes and for practice